Peran Kepribadian Anchor Virtues terhadap Flourishing pada Dosen PNS - Rahmatika, Aufilana; Hapsari, Maharani Tyas Budi (Universitas Muhammadiyah Metro, 2024)
Personality plays a crucial role in influencing an individual's level of flourishing by the subject lecturers in the civil employee. One approach to understanding personality in the flourishing context is the concept of